Spin-up conversion, exchange-interactions, and tailored magnetic properties in coreshell La2NiMnO6of small crystallites - Hissariya R.; Babu S.; Ram S.; Mishra S.K. (My University, 2025)
La2NiMnO6-a ferromagnetic (FM) insulator offers tunable charge carriers and spins useful to devise its multiple properties and applications. In this view, we studied a core-shell La2NiMnO6 (2-3 nm shell on 65 - 80 nm core) of a Ni2+/Ni3+ (d7) to Mn4+/Mn3+ (d4) spin-up conversion - revived a new FM phase-2, raising a spin-density σs = 0.7 s a-1 over the Ni2+/Mn4+ species (phase-1), σs = 0.5 s a-1, i.e. 2.12 μB/f.u. larger spin moment. HRTEM images studied with x-ray diffraction characterizing core-shell structure that plays a crucial role in tuning the high spin FM phase-2 of profound properties. Below 110 K, the dc magnetization and ac magnetic susceptibility Χ(ω, T) reveal a metastable magnetic behavior on an antiferromagnetic canting of a spin-glass nature. The results follow a Vogel-Fulcher type relaxation with a relaxation time τ0 ~ 10-13 s, confirming a spin-glass freezing behavior. Uniquely, FM field of phase-1 controls magnetics of phase 2 of a coupled magnet, modulating joint features with small thermal magnetic hysteresis on heating-cooling cycles. © 2021 IOP Publishing Ltd.